Molecular docking study and molecular dynamics simulation of spice metabolites against main protease enzymes and NSP3 macrodomain SARS CoV-2 - Purwaniati Purwaniati; Asep Roni (Pharmaciana, 2022)
COVID-19 is still a global pandemic. The transmission is very fast and wide. Its prevalence continues to increase. There is no specific antiviral drug for SARS CoV 2 yet. This study aims to find lead compounds from compounds derived from spices that can work as multitarget SARS CoV-2 antivirals. The target of drug action chosen in this study is the main protease enzyme and non-structural protein 3 (NSP3) macrodomain. Antiviral compounds that work on both targets are expected to be more potent. This antivirus will work to inhibit virus replication through main protease inhibition and increase innate immunity through NSP3 macrodomain inhibition. Molecular docking and molecular dynamics simulation were chosen as the methods in this study. Based on the results of molecular docking, it was found that the compound of dauricine, tomentin A, daurisoline, xhantoangelol, rutin and myricetin gave good affinity to both targets. These compounds provide an inhibition constant below 10000 nM or 10 micromolar. Meanwhile, in the molecular dynamics simulation test, it was found that dauricine, rutin, myricetin, and xhantoangelol have good interaction stability with both targets. So from this study, it can be concluded that dauricine, rutin, myricetin and xhantoangelol are potential compounds as lead compounds for SARS CoV-2 antivirals that act on the main protease and the NSP3 macrodomain.